Protective role of hydrogen-rich water on aspirin-induced gastric mucosal damage in rats - Zhang, Jing-Yao (Baishideng Publishing Group Co., Limited, 2014)
AIM: To investigate the role of the hydrogen-rich water (HRW) in the prevention of aspirin-induced gastric mucosal injury in rats. METHODS: Forty male rats were allocated into four groups: normal control group, HRW group, aspirin group, and HRW plus aspirin group. The protective efficacy was tested by determining the gastric mucosal damage score. Malondialdehyde (MDA), superoxide dismutase (SOD), myeloperoxidase (MPO), interleukin (IL)-06 and tumor necrosis factor (TNF)-α in gastric tissues were evaluated. The serum levels of IL-1β and TNF-α were also detected. Histopathology of gastric tissues and localization of Cyclooxygenase 2 (COX-2) were detected using hematoxylin and eosin staining and immunohistochemistry, respectively. RESULTS: Pretreatment with HRW obviously reduced aspirin-induced gastric damage scores (4.04 ± 0.492 vs 2.10 ± 0.437, P < 0.05). The oxidative stress levels of MDA and MPO in the gastric tissues increased significantly in the aspirin-treated group compared with the HRW group (2.43 ± 0.145 vs 1.79 ± 0.116 nmol/mg prot, P < 0.05 and 2.53 ± 0.238 vs 1.40 ± 0.208 U/g tissue, P < 0.05, respectively). HRW could obviously elevated the SOD levels in the gastric tissues (37.94 ± 8.44 vs 59.55 ± 9.02 nmol/mg prot, P < 0.05). Pretreatment with HRW significantly reduced IL-06 and TNF-α in the gastric tissues (46.65 ± 5.50 vs 32.15 ± 4.83 pg/mg, P < 0.05 and 1305.08 ± 101.23 vs 855.96 ± 93.22 pg/mg, P < 0.05), and IL-1β and TNF-α in the serum (505.38 ± 32.97 vs 343.37 ± 25.09 pg/mL, P < 0.05 and 264.53 ± 28.63 vs 114.96 ± 21.79 pg/mL, P < 0.05) compared to treatment with aspirin alone. HRW could significantly decrease the COX-2 expression in the gastric tissues (staining score: 8.4 ± 2.1 vs 2.9 ± 1.5, P < 0.05). CONCLUSION: HRW pretreatment alleviated the aspirin-induced gastric lesions by inhibiting the oxidative stress, inflammatory reaction and reducing the COX-2 in the gastric tissues.